"Mtoto Wa Nyoka Ni Nyoka," The Child of a Snake is a Snake: A Narrative Analysis of Adverse Childhood Experiences and Perpetration of Interpersonal Violence Among Men in Dar es Salaam, Tanzania - Zietz, Susannah (Journal of interpersonal violence, 2022)
Childhood exposure to adversity, including abuse and neglect, is consistently found to be a predictor of intimate partner violence (IPV) and peer violence (PV) perpetration in adulthood. The purpose of this study is to qualitatively examine factors that may facilitate or impede the use of violence among those who have been exposed to adversity early in life. We are particularly interested in protective experiences or environments for these participants. The qualitative data were analyzed through thematic coding and narrative analysis of participant life histories.We found three salient themes: (a) parental acceptance and early attachment is protective for coping with stress with intimate partners in adulthood; (b) certain key life turning points can provide a protective context against violent behavior in adulthood; and (c) poverty in adulthood compromises one?s ability to cope with stress and anger in adulthood.Our findings contextualize the different factors that may affect the behavior of perpetration of interpersonal violence among high-risk men in Dar es Salaam who have been exposed to adversity in childhood. These findings provide important information on the risk and protective factors for interpersonal violence spanning from childhood to adulthood. This study highlights the importance of child development interventions in this situation, both for the primary prevention of child adversity and for promoting resilience and mitigating the effects of childhood adversity that put men at risk for perpetration of interpersonal violence in adulthood.